Intraspecific phenotypic differentiation by habitat depth in deep demersal fish species - Steeds, Natasha; Zulqurnain, Zulqurnain; Regnier, Thomas; Gibb, Fiona; Stirling, David; Hoelzel, A. Rus (Frontiers in Marine Science, 2024)
Introduction Ocean habitat characteristics change with depth. This is due to physical properties such as light, temperature and hydrostatic pressure, but also species community. In some cases, this generates a boundary (e.g. when light is lost in the bathypelagic), and in others it varies continuously (e.g. for hydrostatic pressure). Various studies have noted general morphometric adaptations to living at different depths seen among species, even though vertical migration can cause their ranges to overlap. However, few have looked at intraspecific changes. Methods Here we investigate intraspecific variation for four species of demersal fish that inhabit a broad range of depths (200 m to over 2000 m). We test the hypothesis that intraspecific morphological variation will be similar to that seen among species. Results We find that there are significant phenotypic differences between fish taken at different habitat depths, especially associated with mouth gape size, eye size, body shape and organ mass, despite the potential for vertical migration. However, we find that these patterns vary among species. Discussion We consider the possible drivers and implications for maintaining intraspecific phenotypic differences.